CROSSING IN OPEN WATERS: SOCIAL IMAGINARY OF THE ADVENTURE AND RISK OF BLIND ATHLETES (Fiep Bulletin - online, 2015)
A qualitative and exploratory study about crossings open waters that involved eight blind people from the Benjamin Constant Institute, using semi-structured interviews and Allegory of Animals, allowing the formulation ob projective dreams of their drive ideas. It aims at understanding some of the meanings of that adventure, body orientation and mobility, making explicit the world of meanings that constitute the Social Imaginary of those swimmers. Some symbolic and mystic elements expressed in their speeches were highlighted. Blind people who practice sports in addition to some physical activity enjoy the right of moving independently and autonomously. The free exercise of this practice entitled them to challenge their disabling conditions. Facing the sea in all its extension leads us to imaginative and inspired trips. Whenever the images are subjectively built by perception hints, words and language and not only by the vision organs, the body will be able to feel reality, even if eyes cannot see. That athletes' adventure in the sea is represented by their sensations and images built out of meanings and impregnated of senses. Several speeches are present in the universe of the disabled, supplying hints on how to understand this social imaginary. To reveal these hints brings new discussions and looks. To be heroically reborn out of the waters of the sea, searching strength for daily life represents overcoming, a conquest they make to face the social discrimination from an inclusive perspective. When we interpreted the results we detected three animals. Linked to the trilogy of the elements earth-water-moon, the dog has a psychopomb, clairvoyant, guide, bewitching, second-sighted function. The dolphins symbolize regeneration, divination, wisdom, prudence, displacement, and lord of the navigation. The flight of the bird establishes relationships between heaven and earth, liberation, presage, message from heaven, lightness. The adventure of swimming in open waters allowed us to understand that this imaginary where water is life discovered in the darkness, in regeneration. They move through symbols of clairvoyance, through their internal forces, overcoming, conquest.
Keywords: crossing / adventure / the blind